Leading by Example - Breen, Yellow; Hutchins, Jennifer; Sharp, Marcia (Maine Policy Review, 2018)
Leading by example, three nonprofits faced tough decisions and significant organizational changes to ensure the sustainability and growth of successful leadership programs in Maine. Lessons shared provide insights that may be useful to other nonprofits facing similar challenges.